Hospital services: empowerment of physical disabled people in the construction of spaces available - Antônia Eliana de Araújo Aragão; Lorita Marlena Freitag Pagliuca (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
In Brazil, with regard to public policies for disable persons with barriers in access to health services1, there are challenges for implementation. Depending on the experience as a participant in the design of accessibility of people with physical disabled and/or Sensory Services Health: study of physical and or communication, funded by the Ministry of Health, urged the reflection about the importance of strengthening this population forward the construction of spaces available to hospital services. Facing this, and attempt to break the biomedical model2, we believe that community participation is a sine qua non situation in the process of execution of health policies, highlighting the Empowerment3, understood as involving and strengthening growth in the activation of potential analysis of individuals as to their circumstances of life. In this perspective, motivate Disabled Persons for the construction of spaces available, with views to the autonomy ad safe use of buildings, including furniture and urban equipment, is to ensure basic human rights.